Combining cell‐based therapy and normothermic machine perfusion for kidney graft conditioning has gone one step further. Issue 4 (4th September 2020) - Steichen, Clara; Erpicum, Pauline
Abstract : The authors provide perspectives on the report by Thompson et al. (page 1402 ), highlighing strengths and weaknesses of the experiments using multipotent adult progenitor cells to condition human kidneys during normothermic machine perfusion.